2013
DOI: 10.1111/jnu.12062
|View full text |Cite
|
Sign up to set email alerts
|

Basic Nursing Care: Retrospective Evaluation of Communication and Psychosocial Interventions Documented by Nurses in the Acute Care Setting

Abstract: The identification of psychosocial elements of basic nursing care in the nursing documentation may lead to obtain a deeper understanding of those caring interventions nurses consider essential to represent nurse-patient interactions. The frequency of psychosocial interventions may contribute to delineate basic and advanced nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…However, a number of relational and psychosocial FoC elements were rarely observed, and in general they occurred less frequently than the physical elements, confirming a dominant biomedical focus in acute health care (Feo & Kitson, ). International literature also indicates that nurses rarely discuss a disease's emotional aspects or explore the patient's feelings actively (Kruijver, Kerkstra, Bensing, & Wiel, ), and they rarely report the undertaking of actions to address or improve the patients’ psychosocial needs (Juve‐Udina et al, ). Other studies have also reported the difficulty of nursing students with identifying the patients’ psychosocial and relational needs (Jangland et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of relational and psychosocial FoC elements were rarely observed, and in general they occurred less frequently than the physical elements, confirming a dominant biomedical focus in acute health care (Feo & Kitson, ). International literature also indicates that nurses rarely discuss a disease's emotional aspects or explore the patient's feelings actively (Kruijver, Kerkstra, Bensing, & Wiel, ), and they rarely report the undertaking of actions to address or improve the patients’ psychosocial needs (Juve‐Udina et al, ). Other studies have also reported the difficulty of nursing students with identifying the patients’ psychosocial and relational needs (Jangland et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For studies measuring the presence of staff–patient interactions in nursing documentation, we found only one quantitative study: Juvé‐Udina et al. () evaluated the frequency of documented psychosocial interventions in acute care settings, but only 3.8% of the data material were collected in mental health services. Qualitative studies from different mental health contexts found that nursing documentation primarily comprised nurses' observations of patients' behaviour and provided only limited information about staff–patient interactions (Buus & Hamilton, ; Martin & Street, ).…”
Section: Introductionmentioning
confidence: 99%
“…We searched in Cinahl, Medline, PsycInfo and ProQuest with the combinations of terms shown in Columns 1 and 2 of Table 1. Systematic reviews have identified a range of audit instruments for nursing documentation, but not one had explicit measures for staff-patient interactions or for attunement and empathy (Saranto & Kinnunen, 2009;Wang, Hailey, & Yu, 2011). For studies measuring the presence of staff-patient interactions in nursing documentation, we found only one quantitative study: Juvé-Udina et al (2014) evaluated the frequency of documented psychosocial interventions in acute care settings, but only 3.8% of the data material were collected in mental health services. Qualitative studies from different mental health contexts found that nursing documentation primarily comprised nurses' observations of patients' behaviour and provided only limited information about staff-patient interactions (Buus & Hamilton, 2016;Martin & Street, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…If available at all, reviews selected in the “Nursing Care Field” of the Cochrane reviews refer to very specific subtopics of (non‐) nursing care in distinct patient groups, such as “speech and language therapy for aphasia in stroke patients” (Brady, Kelly, Godwin, & Enderby, ) or “upper limb exercises in breast cancer patients” (McNeely et al., ). Yet, within the growing evidence base of nursing, patients’ basic care needs appears to be one of the most understudied areas in nursing research (Juve‐Udina et al., ; Schneider & Ruth‐Sahd, ). To prioritise basic nursing care, this article aimed to describe and discuss the “Basic Care Revisited” (BCR) research programme.…”
Section: Introductionmentioning
confidence: 99%